Costing for the fashion industry - Evans, Nathalie (Nathalie Nicole Françoise); Jeffrey, Michael 1951- (New York Bloomsbury, 2020)
"A practical, easy-to-use introduction to costing for the fashion industry for general fashion students who lack any accounting experience"--
1. Small and medium-sized (SMEs) clothing businesses -- 2. Risk management -- 3. Global awareness and new markets -- 4. Product cost when sourcing -- 5. The native of clothing manufacture and the need for costing -- 6. The elements of cost -- 7. Costing over periods of time -- 8. Product cost - job costing -- 9. Marginal costing -- 10. Break-even analysis -- 11. Budgeting and standard costing -- 12. The changing nature of cost -- 13. Activity-based costing -- 14. Capital investment decisions.
Previous edition entered under: Michael Jeffrey.
Includes bibliographical references and index.
Keywords: Fashion merchandising; Clothing trade -- Costs